Numerical analysis of energy recovery system for turbocharged internal combustion engines via a parallel compounding turbine - Frigo, Stefano; Francesconi, Marco; Sani, Luca; Antonelli, Marco (Journal of physics. Conference series, 2022)
Increasing energy efficiency requirements mandatory ask for optimizing energy utilization in many devices, which include internal combustion engines. One of the most investigated subjects is the energy recovery from the exhaust, such as turbo-compound systems, which usually consist in a secondary turbine located afterward the turbocharger. Here an alternative arrangement is proposed and analysed via a numerical model. The recovery turbine works in parallel to the main turbine and uses the gasses which would be otherwise wasted through the waste-gate valve, once the set-point boost pressure is reached. The reference case analysed is a 12.4L turbocharged diesel engine, commonly used in marine, road and light railroad applications, with a nominal power of 380kW. The results showed that an overall 8% of power can be gained, without nor increasing the fuel mass flow rate, neither requiring significant modifications to the baseline engine. Moreover, in the case of the recovery system failure, the operation of the engine is not affected, thus resulting in no engine availability reduction. This work also shows a feasible way to convert the mechanical energy delivered by the recovery turbine into electrical energy, by making use of a high-speed electrical generator.